Growth and fosE gene expression in inulin-containing medium of two strains of Lactobacillus casei originated from the human intestinal tract - AMIK CHOIRUL AFIDAH; TUTIK DWI WAHYUNINGSIH; Widodo Widodo (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Authors. 2019. Growth and fosE gene expression in inulin-containing medium of two strains of Lactobacillus casei originated from the human intestinal tract. Biodiversitas 20: 2758-2763. Inulin is a fructooligosaccharide consisting of a fructose monomer with ?- (1,2) glycosidic linkage. The human colon cannot degrade inulin because it lacks the enzyme that degrades ?- (1,2) glycosidic linkage. Lactobacillus casei strain AP is able to grow in inulin, L. casei strain AF grows gradually. The ability to grow in inulin is proposed by the fosE gene, which hydrolyzes ?- (1,2) glycosidic linkage. The present study aimed to detect and measure fosE gene expression in inulin. Extracellular and intracellular inulin and fructose concentrations were calculated using high-performance liquid chromatography. The reduction of inulin concentration in L. casei strain AP was higher than that in L. casei strain AF. Extracellular fructose concentration was lower in L. casei strain AP because fructose from inulin degradation was transported into the cell. No fructose was detected inside Lactobacillus cells. The fosE gene was detected in L. casei strains AP and AF with a length of 229 bp. fosE gene expression was up-regulated 5.9-fold in L. casei strain AP and 1.7-fold in L. casei strain AF and was three times higher in L. casei strain AP than that in L. casei strain AF, suggesting that the former metabolizes inulin better than the latter.